Model Kepuasan Orang Tua/Wali Siswa Berdasarkan Peningkatan Kualitas Pelayanan Sekolah Secara Berkelanjutan (Studi Kasus TK. Bina Mulia) - Muhamad Khaerudin; Srisulistiowati, Dwi Budi; Setiawati, Siti (Journal of Informatic and Information Security, 2021)
Kindergarten. Bina Mulia Cibitung is a school engaged in early childhood education. Customer satisfaction survey is certainly needed to know the response of parents / guardians of students to the quality of service. But during this kindergarten. Bina Mulia has not conducted a survey on the satisfaction of parents of students to the services performed by teachers and administrative personnel. In anticipation of things that the school did not want during this pandemic, the survey was done not directly but online. Respondents to this survey are all parents / guardians of students both still active in school and who have graduated. This research is planned on an ongoing basis with the aim of knowing the level of satisfaction of parents / guardians to school services. In addition, this research aims to produce an online survey application that is integrated with the survey management information system, while the CSI method to measure customer satisfaction. Analysis of survey results is calculated using customer satisfaction index (CSI) method. CSI is a quantitative analysis in the form of a percentage of the number of parents / guardians of students to this service satisfaction survey.